RETRACTED: Das et al. Peer-to-Peer Energy Trading Pricing Mechanisms: Towards a Comprehensive Analysis of Energy and Network Service Pricing (NSP) Mechanisms to Get Sustainable Enviro-Economical Energy Sector. Energies 2023, 16, 2198 - Arnob Das; Susmita Datta Peu; Md. Abdul Mannan Akanda; Abu Reza Md. Towfiqul Islam (Energies)
The journal retracts the article titled “Peer-to-Peer Energy Trading Pricing Mechanisms: Towards a Comprehensive Analysis of Energy and Network Service Pricing (NSP) Mechanisms to Get Sustainable Enviro-Economical Energy Sector” [...]